PROGRAM SEARCH DATA APPLICATIONS IN GOODS STORES WITH BANGUNAN BARU CERAMIC USING VISUAL BASIC 6.0 - Adi Heryanto; Susi Wagiayati, SKom, MMSi (Jurnal Sistem Informasi, 2004)
Writing this on the application of the display contains information about the dataitems in the "CERAMIC SHOP BANGUNAN BARU", and therefore expected thatthe application can provide information quickly, efficiently, and accurately andreliably.In this information display applications the author uses Visual Basic program. VisualBasic is a software that not only limited to building database-based applications, butcan be useful for a variety of other needs.With the application of information display these data are expected in the data-datasearches will be easier and faster in its presentation and accountable to the owners ofthese stores.